Preparation of a Novel Cartridge of SPE Column using a new Surface of Hetrocyclic Azo Ligand with Modified Activated Carbon - Faiq F. Karam (Journal of Global Pharma Technology, 2016)
Disposable cartridges have been created using low-cost activated carbon produced from waste as solid support via using a chemical activation method, and modified with the new tridentate [N.N.O] donor azo ligand to yield a solid-phase sorbent, the thiazole azo 2-[2ــ -( 5-nitro thiazolyl) azo]-4-methyl-5-nitro phenol ( 5-NTAMNP) derived from 2-amino-5-nitrothiazole and 3-methyl-4-nitrophenol by the diazotization operation and the adizonium chloride salt solution of 2-amino-5-nitrothiazole reacting with 3-methyl-4-nitrophenol as a coupling compound in alkaline alcoholic solution. The structure of ligand was identified and confirmed via resorting to various spectroscopic techniques which included, Proton nuclear magnetic resonance, Mass spectrum, UV–visible, Fourier-transform infrared (FTIR), X-Rays diffraction (XRD), the surface nature and morphology and size average and elemental composition of individual ligand particles were examined using a field emission scanning electron microscope (FE-SEM) coupled with an energy dispersive X-ray system (EDX), novel (5-NTAMNP)-modified activated carbon solid-phase sorbent were synthesized and characterized by chemical analysis by using, FT-IR, and XRD techniques and chelating sorbent were used as an adsorbent for the removal and for the determination of a hazardous heavy metallic ions Mn(II), Fe(III), Pb(II), Cu(II), in water under the optimum pH value for complexation with this azo ligand. The new (5-NTAMNP)-modified activated carbon showed highly effective solid phase extraction properties for these metallic ions.Keywords: Activated carbon, NNO donor azo ligand, Solid-phase extraction, Disposable cartridges, SPE.